2011
DOI: 10.1016/j.jchromb.2011.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a UHPLC-FLD analytical method for the simultaneous quantification of aflatoxin B1 and ochratoxin a in rat plasma, liver and kidney

Abstract: addresses of all coauthors: Laura-Ana Corcuera: lcorcuer@alumni.unav.es, María Ibáñez-Vea: mivea@alumni.unav.es, Ariane Vettorazzi: avettora@alumni.unav.es, Adela López de Cerain: acerain@unav.es. 2 ABSTRACTA rapid and simple method for the simultaneous quantification of AFB1 and OTA in rat plasma, liver and kidney by UHPLC-FLD has been successfully validated according to the following criteria: selectivity, stability, linearity, precision, accuracy, recovery, robustness and limits of quantification and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 30 publications
3
20
0
1
Order By: Relevance
“…Chromatograms of blank plasma (a) and liver (d), blank plasma (b) and liver (e) spiked with AFB1 and T-2 (50 ng mL (Table 2). For both mycotoxins in plasma and tissue homogenates, the LLOD and LLOQ were 0.01 and 0.05 ng mL -1 , respectively (Table 2), which were desirable and obviously lower than those obtained in bibliography via UHPLC-FLD approaches 35 .…”
Section: Methods Validationmentioning
confidence: 72%
See 1 more Smart Citation
“…Chromatograms of blank plasma (a) and liver (d), blank plasma (b) and liver (e) spiked with AFB1 and T-2 (50 ng mL (Table 2). For both mycotoxins in plasma and tissue homogenates, the LLOD and LLOQ were 0.01 and 0.05 ng mL -1 , respectively (Table 2), which were desirable and obviously lower than those obtained in bibliography via UHPLC-FLD approaches 35 .…”
Section: Methods Validationmentioning
confidence: 72%
“…First, the same food can be infected or invaded by different mycotoxigenic molds resulting in the co-occurring AFB1 and T-2 even at high concentrations in many geographic origins under optimum environmental conditions [14][15][16] ; Second, co-occurring mycotoxins can reach humans through the various diets and also, through milk, meat and eggs from livestock and poultry animals fed with different mycotoxins contaminated feedstuffs [17][18][19] . The toxic effects, appearing in consumers exposed to co-occurring mycotoxins, are surely in accordance to the possible interactions of concomitantly occurring mycotoxins, which might be antagonistic, additive, or synergistic on different occasions 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The extraction procedure and the UHPLC-FLD quantification 7 method was previously set up and validated for these biological samples, and has been performed as described (Corcuera et al, 2011b).…”
Section: Determination Of Mycotoxins In Plasma Liver and Kidneymentioning
confidence: 99%
“…AFB 1 is nephrotoxic, hepatotoxic, mutagenic, genotoxic, and immunotoxic. [1][2][3][4][5] AFB 1 mediated cell injury may be due to the release of free radicals and these radicals initiate lipid peroxidation (LPO) and a damaging process in biological systems since all cell membranes contain the polyunsaturated fatty acids which are substrates for such a reaction. 6 Kodama et al showed the formation of LPO by AFB 1 .…”
mentioning
confidence: 99%